Symmetry and Economic Invariance - Sato, Ryuzo; Ramachandran, Rama V.; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2014)
Symmetry and Economic Invariance (second enhanced edition) explores how the symmetry and invariance of economic models can provide insights into their properties. Although the professional economist of today is adept at many of the mathematical techniques used in static and dynamic optimization models, group theory is still not among his or her repertoire of tools. The authors aim to show that group theoretic methods form a natural extension of the techniques commonly used in economics and that they can be easily mastered. Part I provides an introduction that minimizes prerequisites including prior knowledge of group theory. Part II discusses recent developments in the field.
Keywords: Economics; Economics -- Methodology; Economics, Mathematical; Economics/Management Science; Economic Theory; Methodology and the History of Economic Thought; Game Theory/Mathematical Methods